Detection and Analysis of melanin pigment in the edible seed coat of some plants - Rajasekaran, Anitha; Kamalakannan, Geetha (Current Botany, 2024)
Melanin is a dark phenolic substance present in plants, animals, and microorganisms. The role of melanin in plants is to offer protection against biotic and abiotic conditions. The other possible functions in plants are unknown. Studying the occurrence of melanin in plants is essential to understand the taxonomic evolution of plants and its application in different fields. The deposition and distribution of Phytomelanin in the seed coat was studied using a light microscopy The seed coats of Phaselous vulgaris (Leguminaceae), Vigna mungo (Fabaceae), Linum usitatissimum (Linaceae), Cicer arietinum (Fabaceae), Vigna unguiculata (Fabaceae), Sesamum indicum (padaliaceae) and Macrotylama uniflorum (Fabaceae) showed the presence of melanin. Among the plant studied, S. indicum and V. mungo had a higher yield of melanin per 5 g of seeds. Melanin was extracted, purified and a confirmatory test was also conducted. UV and FT-IR studies were carried out with purified melanin. V. mungo and P. vulgaris showed no absorbance in the UV spectrum. The Maximum absorbance was found at 276 nm for S. indicum, M. uniflorum at 283 nm, L. usitatissimum at 276.5 nm, and V. unguiculata at 286 nm. It is evident from the study that phytomelanin is present in higher concentrations in S. indicum followed by V. mungo.